2022
DOI: 10.3389/fnins.2022.919440
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Functional Brain Networks Underlies the Handwriting Deficit in Children With Developmental Dyslexia

Abstract: Developmental dyslexia (DD) is a neurological-based learning disorder that affects 5-17.5% of children. Handwriting difficulty is a prevailing symptom of dyslexia, but its neural mechanisms remain elusive. Using functional magnetic resonance imaging (fMRI), this study examined functional brain networks associated with handwriting in a copying task in Chinese children with DD (n = 17) and age-matched children (n = 36). We found that dyslexics showed reduced network connectivity between the sensory-motor network… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 85 publications
0
5
0
Order By: Relevance
“…As we have already pointed out [49], sensorimotor deficits in dyslexia can include postural, oculomotor, motor coordination, and implicit motor learning disorders in dyslexic children and adults [27,34,50,51]. More recent research on dyslexia ( [52], for a recent review), and on motor comorbidities, have, for example, addressed dysfunctions in writing abilities [53,54] and even rhythmic motor competencies [55]. Nevertheless, there is still a consensus that motor difficulties are present in part of the dyslexia population, albeit to a larger extent in children than adults [27,34].…”
Section: Single Vs Multiple-deficit Hypotheses In Dyslexiamentioning
confidence: 99%
“…As we have already pointed out [49], sensorimotor deficits in dyslexia can include postural, oculomotor, motor coordination, and implicit motor learning disorders in dyslexic children and adults [27,34,50,51]. More recent research on dyslexia ( [52], for a recent review), and on motor comorbidities, have, for example, addressed dysfunctions in writing abilities [53,54] and even rhythmic motor competencies [55]. Nevertheless, there is still a consensus that motor difficulties are present in part of the dyslexia population, albeit to a larger extent in children than adults [27,34].…”
Section: Single Vs Multiple-deficit Hypotheses In Dyslexiamentioning
confidence: 99%
“…Recent research on learning disabilities and memory has focused on a range of topics, including the neurobiological basis of these conditions, the impact of technology on memory and learning, and potential interventions. In a study that was carried out by Liu et al (2022) study on changes in functional connectivity in children with dyslexia during visual and phonological processing tasks, functional magnetic resonance imaging (fMRI) was utilized to investigate the neural networks that are involved in the processing of visual and phonological information in children who have dyslexia. The authors found that children with dyslexia showed altered functional connectivity in brain regions associated with phonological processing, suggesting that dyslexia may be related to abnormal neural connectivity.…”
Section: Learning Disabilities: Definition and Interventionsmentioning
confidence: 99%
“…Nonetheless, RD readers could not efficiently deactivate the default mode network for the more challenging foreign speech imitation to a greater degree. The default mode network has been found to play an important role in learning (Howard-Jones, Jay, Mason, & Jones, 2016;Lin et al, 2017), and its abnormality has been reported in developmental disorders, such as RD (Boros et al, 2016;Liu, Li, Bi, Xu, & Yang, 2022;Mateu-Estivill et al, 2021), ASD (Assaf et al, 2010;Murdaugh et al, 2012;Washington et al, 2014), and ADHD (Castellanos & Proal, 2012;Qiu et al, 2011;Uddin et al, 2008). In a recent study, the default mode network showed the largest developmental changes in brain signal complexity during the period of 6-13 years of age, compared to 5 other networks, namely, vision, motor, dorsal attention, ventral attention and frontal-parietal network (Jia et al, 2023), suggesting that the development of the default mode network might be more influenced by learning experiences and environment than the other networks.…”
Section: Behavioral and Neurological Abnormality During Speech Percep...mentioning
confidence: 99%